Gene activation of CEBPA using saRNA: preclinical studies of the first in human saRNA drug candidate for liver cancer - Reebye,V; Huang,K-W; Lin,V; Jarvis,S; Cutilas,P; Dorman,S; Ciriello,S; Andrikakou,P; Voutila,J; Saetrom,P; Mintz,PJ; Reccia,I; et al. (Oncogene, 2018)
Liver diseases are a growing epidemic worldwide. If unresolved, liver fibrosis develops and can lead to cirrhosis and clinical decompensation. Around 5% of cirrhotic liver diseased patients develop hepatocellular carcinoma (HCC), which in its advanced stages has limited therapeutic options and negative survival outcomes. CEPBA is a master regulator of hepatic function where its expression is known to be suppressed in many forms of liver disease including HCC. Injection of MTL-CEBPA, a small activating RNA oligonucleotide therapy (CEBPA-51) formulated in liposomal nanoparticles (NOV340- SMARTICLES) upregulates hepatic CEBPA expression. Here we show how MTL-CEBPA therapy promotes disease reversal in rodent models of cirrhosis, fibrosis, hepatosteatosis, and significantly reduces tumor burden in cirrhotic HCC. Restoration of liver function markers were observed in a carbon-tetrachloride-induced rat model of fibrosis following 2 weeks of MTL-CEBPA therapy. At 14 weeks, animals showed reduction in ascites and enhanced survival rates. MTL-CEBPA reversed changes associated with hepatosteatosis in non-alcoholic methionine and cholic-deficient diet-induced steaotic liver disease. In diethylnitrosamine induced cirrhotic HCC rats, MTL-CEBPA treatment led to a significant reduction in tumor burden. The data included here and the rapid adoption of MTL-CEBPA into a Phase 1 study may lead to new therapeutic oligonucleotides for undruggable diseases.